Night lamp brightness controller system - Siti Hanum Surya, Ibrahim (2009)
Night Lamp Brightness Controller System is designed as an intelligent street light. This is because this system can sense day or night, sense if there is any motion or not and can control the brightness of the lamp in two condition, dim or full brightness. The brain for this system is PIC16178 77. Firstly, Light Dependent Resistor (LDR) sensor will sense day or night. If the sensor sense night, PlC microcontroller will switch on the Passive Infrared (PIR) sensor and lamp in dim condition and but if it day, there is nothing happen towards the system. Next, when PIR sensor senses the motion or movement, PlC microcontroller will switch the condition of lamp from dim to full brightness. The lamp will be in full brightness condition until the PIR sensor did not sense any movement anymore and it will back to dim conditon. Next when LDR sensor senses the intensity of light from sun, the system will turn the lamp and PIR sensor off. Lastly, this system will loop to the initial condition.